The microenvironment reprograms circuits in tumor cells - Cai, Qingchun (Mol Cell Oncol, 2015)
In the course of multistep oncogenesis, initially normal cells acquire several new functions that render them malignant. We have recently demonstrated that the peritoneal microenvironment promotes resistance to anoikis in ovarian cancer cells by reprogramming SRC/AKT/ERK signaling and metabolism. These findings have prognostic and therapeutic implications.